2021
DOI: 10.1155/2021/6091585
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Eriodictyol on Retinoblastoma via the PI3K/Akt Pathway

Abstract: Retinoblastoma (RB) is one of the most common intraocular malignancies in children, which causes vision loss and even threatens life. Eriodictyol is a natural flavonoid with strong anticancer activity. Some studies have shown that eriodictyol exerts anticancer effects in glioma, colon cancer, and lung cancer; however, no studies have reported the anticancer effects of eriodictyol on RB. Therefore, the aim of this study was to investigate the anticancer activity of eriodictyol against the RB Y79 cell line and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…It was further demonstrated that eriodictyol acts as an innovative insulin secretagogue with a glucose-dependent insulintropic activity via a cAMP/PKA pathway as an evidence from in vitro and in vivo model [227]. It was further reported that eriodictyol inhibits the invasion, proliferation, migration, and stimulation of apoptosis in retinoblastoma by regulating the PI3K/Akt pathway [228].…”
Section: Eriodictyolmentioning
confidence: 95%
“…It was further demonstrated that eriodictyol acts as an innovative insulin secretagogue with a glucose-dependent insulintropic activity via a cAMP/PKA pathway as an evidence from in vitro and in vivo model [227]. It was further reported that eriodictyol inhibits the invasion, proliferation, migration, and stimulation of apoptosis in retinoblastoma by regulating the PI3K/Akt pathway [228].…”
Section: Eriodictyolmentioning
confidence: 95%
“…A number of mechanisms are responsible for the enhanced expression of MMP-2 and MMP-9 in retinoblastoma, and thus the promotion of proliferation, invasion, migration of retinoblastoma cells: these include Wnt/β-catenin, NF-κB, PI3K, and Akt pathway activation, the upregulation of HMGA2 gene expression, as well as elevated expression of suppressor of Zeste 12 homolog (SUZ12), a component of the polycomb group protein [60][61][62][63][64]. Nevertheless, a decline in MMP production and activity results in significant inhibition of retinoblastoma development and progression [65][66][67][68].…”
Section: Retinoblastomamentioning
confidence: 99%
“…In an animal model of UM, curcumin treatment resulted in lowered expression of MMP-2 and MMP-9 at both the mRNA and protein level in cancer cells, causing a reduction in tumor size [202]. Eriodictyol, a natural dihydroflavonoid, caused significant inhibition of migration and invasion of retinoblastoma cells; this resulted from downregulation of MMP-2 and MMP-9 protein expression and blockage of the Akt and PI3K signaling pathways [64].…”
Section: Natural Agentsmentioning
confidence: 99%
“…As an embryonal malignancy originating from the nuclear layer of the retina, retinoblastoma (RB) is one of the most common intraocular malignancies in children with genetic susceptibility (Rushlow et al, 2013). Globally, there are 7000 to 8000 new cases and 3000 to 4000 deaths every year (Liu et al, 2019; Wen et al, 2021). Surgical resection, chemotherapy, and radiotherapy are the most commonly used treatment strategies, but the patients with recurrent or metastatic RB still have an extremely poor clinical outcome (Allaman‐Pillet & Schorderet, 2021).…”
Section: Introductionmentioning
confidence: 99%